PENINGKATAN KEMANDIRIAN EKONOMI IBU RUMAH TANGGA MELALUI DEMONSTRASI PEMBUATAN SABUN CUCI PIRING - Lili Andriani; Santi Perawati; Deny Sutrisno; Yuliawati Yuliawati (Universitas Muhammadiyah Tapanuli Selatan, 2020)
Dishwashing soap is a daily requirement of housewives. Solvents can be manufactured on a home scale using materials and methods that are easy to do. The activity of making dish soap can increase the economic independence of mothers who are around the hallway of Mangga Besar village Wijaya Pura in Jambi Selatan, Jambi City. The method used for community service activities is through demonstration directly in front of the participants ' mothers. A total of 20 enthusiastic participants participated in the events ranging from the preparation of materials to packaging. It also examined the safety aspects of chemicals used and analysis of the price calculation of production and sales calculations.